Ion demagnetization in the magnetopause current layer observed by MMS. Issue 10 (30th May 2016) - Wang, Shan; Chen, Li‐Jen; Hesse, Michael; Gershman, Daniel J.; Dorelli, John; Giles, Barbara; Torbert, Roy B.; Pollock, Craig J.; Lavraud, Benoit; Strangeway, Robert; Ergun, Robert E.; Burch, Jim; et al.
Abstract: We report ion velocity distribution functions (VDFs) observed by Magnetospheric Multiscale Mission (MMS) and present evidence for demagnetized ion Speiser motion during magnetopause reconnection. The demagnetization is observed in the vicinity of the X line, as well as near the current sheet midplane about tens of ion skin depths ( di ) away from the X line. Close to the X line before the outflow is built up, the VDFs are elongated, and the elongated part of VDFs rotates from the out‐of‐plane current direction toward the outflow directions downstream from the X line. Farther downstream, demagnetized ions exhibit a characteristic half‐ring structure in the VDFs, as a result of the mixture of ions that have experienced different amounts of cyclotron turning around the magnetic field normal to the current sheet. Signatures of acceleration by electric fields are more pronounced in the VDFs near the X line than downstream. Key Points: Magnetosheath ions are demagnetized near the magnetopause reconnection X line and tens of ion skin depths downstream The distributions with demagnetized ions elongate in the out‐of‐plane direction and rotate toward the outflow direction Signatures of acceleration by reconnection electric fields are more pronounced near the X line than downstream